Site- and energy-selective slow-electron production through intermolecular Coulombic decay - Gokhberg, Kirill; Kolorenč, Přemysl; Kuleff, Alexander I; Cederbaum, Lorenz S (Nature, 2014)
Irradiation of matter with light tends to electronically excite atoms and molecules, with subsequent relaxation processes determining where the photon energy is ultimately deposited and electrons and ions produced. In weakly bound systems, intermolecular Coulombic decay (ICD) enables very efficient relaxation of electronic excitation through transfer of the excess energy to neighbouring atoms or molecules that then lose an electron and become ionized. Here we propose that the emission site and energy of the electrons released during this process can be controlled by coupling the ICD to a resonant core excitation. We illustrate this concept with ab initio many-body calculations on the argon-krypton model system, where resonant photoabsorption produces an initial or 'parent' excitation of the argon atom, which then triggers a resonant-Auger-ICD cascade that ends with the emission of a slow electron from the krypton atom. Our calculations show that the energy of the emitted electrons depends sensitively on the initial excited state of the argon atom. The incident energy can thus be adjusted both to produce the initial excitation in a chosen atom and to realize an excitation that will result in the emission of ICD electrons with desired energies. These properties of the decay cascade might have consequences for fundamental and applied radiation biology and could be of interest in the development of new spectroscopic techniques.